2018
DOI: 10.1021/acs.nanolett.7b04722
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable Skyrmion Logic Gates

Abstract: Magnetic skyrmion, a nanosized spin texture with topological property, has become an area of significant interest due to the scientific insight that it can provide and also its potential impact on applications such as ultra-low-energy and ultra-high-density logic gates. In the quest for the reconfiguration of single logic device and the implementation of the complete logic functions, a novel reconfigurable skyrmion logic (RSL) is proposed and verified by micromagnetic simulations. Logic functions including AND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
197
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(198 citation statements)
references
References 31 publications
(44 reference statements)
0
197
0
1
Order By: Relevance
“…In 2016, Xing et al [194] numerically demonstrated the NAND and NOR gates by using both domain walls and skyrmions. In 2018, Luo et al [195]…”
Section: Information Computing: Transistor-like Devices and Skyrmionimentioning
confidence: 99%
“…In 2016, Xing et al [194] numerically demonstrated the NAND and NOR gates by using both domain walls and skyrmions. In 2018, Luo et al [195]…”
Section: Information Computing: Transistor-like Devices and Skyrmionimentioning
confidence: 99%
“…In the following we will apply the Hamiltonian description given by Eqs. (7) and (10) to the dynamics of skyrmions and antiskyrmions. First we review the steady translational motion for rigid topological structures using this approach, and second we apply the technique to study the breathing mode.…”
Section: Effective Hamiltonian Descriptions For Magnetic Skyrmionsmentioning
confidence: 99%
“…Skyrmionic devices promise exceptional electrical efficiency -skyrmions can be directly driven by ultra-low current densities, and even controlled in the absence of current by static magnetic field gradients [3,4]. Their small size and unusual dynamics allow for their utilization in conventional computers, which has prompted a wide study of skyrmionic re-implementations of arithmetic logic units and memory storage devices [5,6]. Additionally, recent studies suggest that skyrmions could find use in exotic devices such as stochastic and reservoir computers [7,8].…”
Section: Introductionmentioning
confidence: 99%